Da pecuária à lavoura: transformações socioculturais, ambientais e produtivas com o avançar dos gringos no Pampa, estudo em São Martinho da Serra/RS - Benetti, Igor Binotto (2024)
The main objective of this work is to understand the sociocultural, environmental and productive transformations that have occurred in the municipality of São Martinho da Serra/RS since the arrival of a group of descendants of Italian immigrants from the Fourth Immigrant Colony. The group investigated today occupies most of the agrarian territory of the municipality, based on soybean cultivation. Before the arrival of the group, this territory belonged to large landowners and family ranchers based on extensive cattle raising in the countryside characteristic of the Pampean biome. To understand these transformations, the research was based on the following specific objectives 1) to understand the process of productive restructuring underway in the country that led to the decline of cattle ranching in the Pampas of Rio Grande do Sul and made possible the entry of new agents in their areas (such as the families of the surveyed group); 2) reconstruct the trajectories of the families to understand how a given economic and cultural capital structure tends to impose a particular mode of reproduction; 3) analyze the internal dynamics of the families and how this contributes to investments and business expansion; 4) demonstrate the consequences of the occupation of the agrarian territory by the investigated group in relation to socio-cultural, environmental and productive transformations in the proposed spatial area. For this purpose, the methodology used is based on a qualitative study of the trajectories of seven families descended from Italian immigrants who migrated from Quarta Colônia/RS to São Martinho da Serra/RS in the 1980s and who today are considered medium and large soybean producers in the municipality. The families chosen cultivate at least 300 hectares of their own and/or rented land. The methodological tools used were secondary data from IBGE and MapBiomas, as well as semi- structured interviews and direct observation by the research group. Major environmental transformations in the landscape were identified, especially the conversion of native pastures into soybean plantations, reaching approximately 80% of the agricultural territory, as well as the suppression of traditional activities such as cattle and sheep raising; decrease in the number of people employed in rural areas; decrease in the rural and total population of the municipality; concentration of land; decrease in agricultural establishments; considerable increase in municipal GDP and little hiring of rural workers from the municipality to the detriment of external labor.